Gestational and Lactational Exposure to the Emergent Alternative Plasticizer 1, 2-Cyclohexane Dicarboxylic Acid Diisononyl Ester (DINCH) Impairs Lipid Metabolism to a Greater Extent Than the Commonly Used Di(2-Ethylhexyl) Phthalate (DEHP) in the Adult Rat Mammary Gland. (21st July 2022) - Crobeddu, Bélinda; Jutras-Carignan, Antoine; Kolasa, Élise; Mounier, Catherine; Robaire, Bernard; Plante, Isabelle
Abstract: Due to their endocrine disruption properties, phthalate plasticizers such as di(2-ethylhexyl) phthalate (DEHP) can affect the hormone-dependent development of the mammary gland. Over the past few years, DEHP has been partially replaced by 1, 2-cyclohexane dicarboxylic acid diisononyl ester (DINCH) which also have potential endocrine disrupting properties. The goal of the present study is to understand the impact of a gestational and lactational exposure to DEHP and DINCH on mammary gland development using Sprague Dawley rats. Both plasticizers altered the adipocytes of the mammary gland fat pad of adult progeny, as demonstrated by a decrease in their size, folding of their membrane, and modulations of the lipid profiles. DEHP treatments decreased the expression of Rxrα and Scd1 at the low and high dose, respectively, but did not affect any of the other genes studied. DINCH modulation of lipid metabolism could be observed at puberty by a decreased expression of genes implicated in triglyceride synthesis, lipid transport, and lipolysis, but by an increased expression of genes of the β-oxidation pathway and of genes involved in lipid storage and fatty acid synthesis at adulthood, compared with control and DEHP-treated rats. A strong upregulation of different inflammatory markers was observed following DINCH exposure only. Together, our results indicate that a gestational and lactational exposure to DINCH has earlier and more significant effects on lipid homeostasis, adipogenesis, and the inflammatory state of the adult mammary gland than DEHP exposure. The long-term consequence of these effects on mammary gland health remained to be determined.